Studies in public opinion : attitudes, nonattitudes, measurement error, and change - Saris, W.E., 1943-; Sniderman, Paul M., 1941- (Princeton University Press, 2018)
In democratic societies, opinion polls play a vital role. But it has been demonstrated that many people do not have an opinion about major issues--the "nonattitudes" problem. Also, the framing of questions in different ways can generate very different estimates of public opinion--the "framing" effect. Both dilemmas raise questions about the competence of ordinary citizens to play the role a democratic society ostensibly expects of them. Although the impact of some factors is well established, particularly political information and sophistication, much is yet to be understood. Building on and reaching beyond themes in the work of Philip Converse, one of the pioneers in the study of public opinion, Studies in Public Opinion brings together a group of leading American and European social scientists to explore a number of new factors, with a particular emphasis on the structure of political choices. In twelve chapters that reflect different perspectives on how people form political opinions and how these opinions are manipulated, this book offers an unparalleled view of the state-of-the-art research on these important questions as it has developed on two continents. The contributors include Matthew K. Berent, Jaak Billiet, George Y. Bizer, Paul R. Brewer, John Bullock, Danielle Bütschi, Michael Guge, Hanspeter Kriesi, Jon A. Krosnick, Milton Lodge, Michael F. Meffert, Peter Neijens, Willem E. Saris, Paul M. Sniderman, Marco R. Steenbergen, Marc Swyngedouw, Sean M. Theriault, William van der Veld, Penny S. Visser, Hans Waege, and John Zaller.